Hubungan Antara Tingkat Kecemasan DenganKualitas Hidup Lanjut Usia Di PantiWredha Darma Bhakti PajangSurakarta - Suryani, Ayu, Fahrun Nur Rosyid, S.kp., M.Kes (2016)
Elderly were vulnerable to the emergence of problems both economic issues, health, psychological and social in which the condition was one of them causes anxiety in the elderly. Anxiety experienced by the elderly corroborated also by lowering the physical condition of the elderly have an impact on quality of life of the elderly. From preliminary studies Panti Wredha Darma Bhakti Pajang , elderly who complain live a life away from their families to make the elderly feel uneasy This study aims to determine the relationship between the level of anxiety and quality of life of elderly in Hospice Pajang Darma Bakti Surakarta. This research was analytic and cross-sectional design. Research sample was 58 elderly people at Panti Wredha Dharma Bhakti Pajang Surakarta with total sampling accidental. Collecting data using questionnaires were analyzed using Spearman rank correlation test. The results were obtained Rs -0269 (p-value = 0.041), thus H0 rejected. Conclusion of the study were (1) the level of anxiety mostly elderly was moderate, (2) the level of quality of life of the elderly was moderate, and (3) there was a relationship with the anxiety level of the quality of life of elderly in Hospice Darma Bakti Surakarta.